2018
DOI: 10.1016/j.neuroscience.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Distribution of DEK Protein in Corticolimbic Circuits Associated with Learning and Memory in Adult Male and Female Mice

Abstract: DEK, a chromatin-remodeling gene expressed in most human tissues, is known for its role in cancer biology and autoimmune diseases. DEK depletion in vitro reduces cellular proliferation, induces DNA damage subsequently leading to apoptosis, and down-regulates canonical Wnt/β-catenin signaling, a molecular pathway essential for learning and memory. Despite a recognized role in cancer (non-neuronal) cells, DEK expression and function is not well characterized in the central nervous system. We conducted a gene ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 67 publications
2
21
0
Order By: Relevance
“…Notably, for all queried forebrain and hindbrain regions (e.g., various frontal cortical areas, striatum, amygdala, hippocampus, cerebellum), DEK mRNA expression was most prominent during the fetal developmental period compared to other developmental stages (adolescent, adult, elderly), suggesting a potential role in neural development. Consistent with these findings, we reported that DEK protein expression is ubiquitously expressed throughout the adult murine brain, with prominent expression in the medial prefrontal cortex, hippocampus proper, and amygdala in both sexes (Ghisays et al 2018). DEK is also robustly expressed in the developing mouse brain (unpublished findings).…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Notably, for all queried forebrain and hindbrain regions (e.g., various frontal cortical areas, striatum, amygdala, hippocampus, cerebellum), DEK mRNA expression was most prominent during the fetal developmental period compared to other developmental stages (adolescent, adult, elderly), suggesting a potential role in neural development. Consistent with these findings, we reported that DEK protein expression is ubiquitously expressed throughout the adult murine brain, with prominent expression in the medial prefrontal cortex, hippocampus proper, and amygdala in both sexes (Ghisays et al 2018). DEK is also robustly expressed in the developing mouse brain (unpublished findings).…”
Section: Introductionsupporting
confidence: 75%
“…Although DEK mRNA expression has been reported in the human brain (Kroes et al 2000), DEK protein localization with other cell types in human brain has yet to be examined. However, RNASeq analysis identified DEK in astrocytes and neurons, amongst other cell types, in rodent frontal cortex (Zhang et al 2014), and using immunohistochemistry, we report that DEK is co-expressed with neuronal, astroglial, and microglial markers in the hippocampus, albeit to varying degrees (Ghisays et al 2018).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our group was the first to associate central nervous system-relevant diseases, such as AD, with decreased expression of the chromatin-binding protein DEK (Ghisays et al, 2018 ). Still, the cellular and molecular relevance of DEK expression in the brain is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, a gene ontology analysis by our group found that AD, dementia, and other age-associated anomalies had transcriptomic signatures associated with DEK loss in human cells (Ghisays et al, 2018 ). Also, using human postmortem brain samples we found that lower DEK protein expression in the anterior cingulate cortex was correlated with increasing dementia severity in women, but not men (O’Donovan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%